Dietary glycated protein modulates the colonic microbiota towards a more detrimental composition in ulcerative colitis patients and non-ulcerative colitis subjects - Mills, D.J.S; Tuohy, K.M; Booth, J; Buck, M; Crabbe, M.J.C; Gibson, G.R; Ames, J.M (Journal of applied microbiology, 2008)
To investigate the effect of native, heated and glycated bovine serum albumin (BSA) on the ulcerative colitis (UC) and non-UC colonic microbiota in vitro. Continuous flow culture (CFC) models of the human colonic microbiota inoculated with faeces from UC and non-UC volunteers were maintained on BSA as growth substrate. Changes in bacterial populations and short-chain fatty acids were determined. UC and non-UC microbiota differed significantly in microbial populations, with elevated numbers of sulfate-reducing bacteria (SRB) and clostridia in the microbiota from UC patients. Compared with native BSA, glycated BSA modulated the gut microbiota of UC patients in vitro towards a more detrimental community structure with significant increases in putatively harmful bacteria (clostridia, bacteroides and SRB; P < 0·009) and decreases in dominant and putatively beneficial bacterial groups (eubacteria and bifidobacteria; P < 0·0004). The levels of beneficial short-chain fatty acids were significantly decreased by heated or glycated BSA, but were increased significantly by native BSA. The UC colonic microbiota maintained in CFC was significantly modified by glycated BSA. Results suggest that dietary glycated protein may impact upon the composition and activity of the colonic microbiota, an important environmental variable in UC.